An effective approach for non-singular trajectory generation of a 5-DOF hybrid machining robot. (April 2023) - Li, Guangxi; Liu, Haitao; Huang, Tian; Han, Jiale; Xiao, Juliang
Highlights: A postprocessing stage-based non-singular tool trajectory generation approach for a hybrid robot is proposed. A S-curve weighting algorithm for the C-axis path optimization which can be integrated into the CNC system is developed. An efficient feedrate scheduling method with the drive limits is proposed to achieve rapid yet smooth movement in the neighborhood of singularity. The orientation accuracy can be improved by setting adequate cone angle and feedrate value in the proposed singularity avoidance approach. The effectiveness of the proposed approach is verified by simulations and experiments on the TriMule-800 hybrid robot. Abstract: By taking a newly developed 5-DOF (degree of freedom) hybrid robot as an exemplar, this paper presents a novel and effective approach for non-singular tool trajectory generation. Based upon singularity analysis via inverse kinematics, an algorithm for the C-axis path optimization is developed using the weighted S-curve. Incorporated singular domain detection with the C-axis angle correction, the algorithm can easily be programmed and embedded into the CNC (computer numerical control) system as a postprocessing module and works in real-time. Then, an offline feedrate scheduling method is proposed by considering the drive and geometric accuracy constraints, allowing the rapid yet smooth movement in the neighborhood of singularity to be achieved. Additionally, it is found that the orientation accuracy can be improved by setting adequate cone angle and feedrate value. The results of both simulations and experiments on a prototype machine show that the C-axis can follow the non-singular tool trajectory well with relatively high rotary speed to pass through the singular domain, thereby verifying the effectiveness of the proposed approach. Graphical abstract: Image, graphical abstract